The digestibility of gelatin complexed with propylene glycol alginate - Mohamed, Suhaila; Stainsby, George (Elsevier, 1985)
The hydrolysis of gelatin and its thermostable complexes with propylene glycol alginate by trypsin and pepsin at 37°C was monitored using ninhydrin and trinitrobenzene sulphonic acid (TNBS). The rate of breakdown of the complexes was the same as that of gelatin alone under these conditions, even though almost a fifth of the ε-amino groups are covalently bonded to polysaccharide. The TNBS method was simpler and more reproducible than the ninhydrin method.